The application of Florpyrauxifen-benzyl 25 g/L, a new auxin synthetic herbicide, to control and inhibit the growth of water hyacinth weed (Eichhornia crassipes (Mart). Solms) - Rezkia, Nita Nur; Kurniadie, Denny; Widayat, Dedi (Universitas Padjadjaran, 2023)
Water hyacinth is an invasive species that spreads rapidly and causes several issues in aquatic habitats; therefore, efforts are required to eradicate weeds in aquatic ecosystems. Aquatic weed control in Indonesia using herbicide is very limited, so it can be an alternative for aquatic weed control management. This research goal was to examine the effectiveness of the herbicide with active agent Florpyrauxifen-benzyl 25 g/L in controlling and inhibiting the rapid growth of (E. crassipes). This research was carried out at the Ciparanje Greenhouse and Weed Science Laboratory, Faculty of Agriculture Universitas Padjadjaran, West Java, Indonesia, from August to October 2022. The experiment utilized a randomized block design (RBD) with eight treatments and four replications. The treatments consisted of herbicides with active ingredients Florpyrauxifen-benzyl 25 g/L doses of 5, 15, 25, 35, 45, herbicide 2,4-D DMA 825 g/L (1200), Penoxsulam 25 g/L (12.5) (g a.i/ha), and Control (Without Herbicide). According to the experiments, E. crassipes was effectively inhibited and controlled by the herbicide Florpyrauxifen-benzyl 25 g/L at a dose of 5 g a.i./ha. Florpyrauxifen-benzyl 25 g/L herbicide can inhibit relative growth rate, doubling time, number of leaves and clumps of E. crassipes up to 6 WAA.